Cancer across the ages: a narrative review of caregiver burden for patients of all ages. Issue 6 (10th August 2020) - Junkins, Courtney C.; Kent, Erin; Litzelman, Kristin; Bevans, Margaret; Cannady, Rachel S.; Rosenberg, Abby R.
Abstract: Problem Identification: Approximately 2.8 million Americans care for an individual with cancer. Because the literature typically describes caregiving experiences within patient age-groups (e.g., pediatrics, geriatrics), the purpose of this narrative review was to describe common and unique burdens and distress among caregivers of cancer-patients of different ages. Literature Search: We identified representative peer-reviewed manuscripts related to caregivers of pediatric, adolescent, young-, middle-, and late-adult oncology patients. We combined search terms "caregiver" and "cancer" with "burden, " "distress, " and/or age-related terms ("pediatric" or "geriatric"). Included studies focused on factors of caregiver-burden and distress. Data Evaluation/Synthesis: Universal cancer-caregiving experiences include negative impacts on work-productivity, finances, social-/family-dynamics, and physical/emotional health. Age-related life experiences shape outcomes; pediatric caregivers may have fewer financial resources, whereas concurrent comorbidities create challenges for geriatric caregivers. Conclusions: Caregiving for cancer patients has universal, shared, and patient age-specific burdens. Implications for Practice: Supportive care based on patient-age may improve caregiver well-being.